ANESTHETIC MANAGEMENT OF PATIENT WITH SYSTEMIC SCLERODERMA SCHEDULED FOR RIGHT LOWER LOBE RESECTION OF THE LUNG - Trposka Poposka A.; Kuzmanovska B.; Kokareva A.; Naumovski F.; Stojanoski S.; Jovanovski Srceva M. (Department of Anesthesia and reanimation, Faculty of Medicine, Ss. Cyril and Methodius University, Skopje Macedonia, 2020)
Progressive systemic sclerosis (PSS) or scleroderma is rare progressive fibrotic disorder of the connective tissue. Together with the connective tissue changes, atrophy of the skin, the involvement of various internal visceral organs may be present in these patients, as well. Not rarely, involvement of the alimentary tract, lungs, heart, kidney, CNS, the presence of the autoantibodies, collagen deposition on different body parts, together with the possible profound vascular hypersensitivity, are reported separately and in combination as possible anesthesiology challenges, sometimes even reported with detrimental outcome. We present a case of a successful anesthesiology management of a patient with PSS undergoing thoracic surgery and we discuss facts from the literature about this disease’s issues and anesthesi